HUMANISTIC IDEAL OF M. I. PIROGOV - Lavrenchuk, Yuriy M. (Educological discourse, 2014)
The article analyses M.I. Pirogov’s pedagogical views in the light of humanistic pedagogy and pedagogical anthropology. The analysis of M.I. Pirogov’s requirements on the organization of the educational process has been done. The content and specific features humanistic orientation of M.I. Pirogov’s views have been revealed. The scientist’s humanistic ideal  has been analyzed. The relevance of humanistic ideal of M. Pirogov has been proved.